Descriptive, Prospective Observational Study- Studying Possible Prediction Factors for Disease Severity and Progression among a Sample of COVD 19 Patients in Iraq - Duaa Mohammed Habeeb; Zinah M. Anwer (College of Pharmacy University of Baghdad, 2022)
Abstract Coronavirus has affected many people around the world and caused an increase in the number of hospitalized patients and deaths. The prediction factor may help the physician to classify whether the patient needs more medical attention to decrease mortality and worsening of symptoms. We aimed to study the possible relationship between C reactive protein level and the severity of symptoms and its effect on the prognosis of the disease. And determine patients who require closer respiratory monitoring and more aggressive supportive therapies to avoid poor prognosis. The data was gathered using medical record data, the patient's medical history, and the onset of symptoms, as well as a blood sample to test the C-reactive protein level. The patients were divided into three groups based on the severity of the disease.  A prospective cohort study of 246 patients over the age of 18 years discovered that c-reactive protein levels were significantly higher in more severe cases than in mild cases, and that older patients with high levels of AST, TSB, Urea, Creatinine, and CRP were associated with the need for a high flow of oxygen, an intensive care unit, a longer length of hospitalization, and a have a high mortality rate. The study concluded several predictor factors for the disease (COVID-19) severity, duration of hospitalization, ICU admission and need for oxygen therapy.